Mobile application development for event and classroom activities management - Guo, Manting (Nanyang Technological University, 2020)
Most events and activities in NTU are being managed manually, resulting in mundane and repetitive works for the teaching staff. This can be problematic due to reasons such as human error and time wastage. For this project, it focuses on improving the attendance taking of everyday classes in NTU. Attendance taking is important because it is beneficial to the learning process for both teachers and students. Teachers can use it as a useful indicator of the quality of their classes. Furthermore, tracking of attendance helps motivate university students to stay consistent in their learning by attending all their classes. The project aims to create an Android based phone application to assist in digitizing attendance taking in NTU that can be implemented fast. As such, the current practice of identifying students using the school matriculation card is maintained but improved, by giving the manual tasks to an Android application. The application uses OCR to identify students by scanning their matriculation cards with the Android phone’s camera. Attendance is marked for class lists preloaded by the user. These class lists are given to the teaching staff at the start of every semester. The application also keeps track of recurring events such as weekly classes for a class group and plots the attendance data in a chart for better visualisation.